Evaluating e-learning among automotive small-medium suppliers: 1. Developing an evaluation tool kit. (6th February 2006) - Chanaron, Jean-Jacques
The two articles deal with the complex issue of evaluating e-learning and benchmarking it with traditional face-to-face training. It is based on the implementation of an experimental e-learning platform dedicated to SMEs within the automotive supply chain. The first paper presents the evaluation tool kit that has been specifically designed from an extensive literature survey. The second part presents the results of the evaluation of the experimental e-learning platform and courses by trainees, tutors, managers and directors who have been involved in the trial sessions.